1992
DOI: 10.1902/jop.1992.63.7.637
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nd:YAG Laser Exposure on Root Surfaces When Used as an Adjunct to Root Planing: An In Vitro Study

Abstract: The purpose of this study was to evaluate the effects of Nd:YAG laser treatment on root surfaces in vitro when used alone or in combination with conventional scaling and root planing. The study population consisted of 18 unerupted third molars, each with a 3 mm diameter treatment site outlined on the root surface. Three specimens were randomly assigned to each of 6 different treatment groups: 1) untreated control; 2) root planed only; 3) laser treated only using 1.25 W of energy; 4) laser treated only using 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0
5

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 7 publications
4
62
0
5
Order By: Relevance
“…(24) also observed smear layer, some debris, collagen and numerous surface depressions apparently corresponding to the opening sites of dentinal tubules on root planed surfaces. At fluences of appn)ximately I J/cm2, and energy densities of 370-450J/cm2, Morlock et al (25) were unable to achieve a clean root surface by Nd:YAG laser irradiation followed by root planing. A scaly smear layer was observed resembling closely the smear layer apparent after root planing only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(24) also observed smear layer, some debris, collagen and numerous surface depressions apparently corresponding to the opening sites of dentinal tubules on root planed surfaces. At fluences of appn)ximately I J/cm2, and energy densities of 370-450J/cm2, Morlock et al (25) were unable to achieve a clean root surface by Nd:YAG laser irradiation followed by root planing. A scaly smear layer was observed resembling closely the smear layer apparent after root planing only.…”
Section: Discussionmentioning
confidence: 99%
“…Nd:YAG laser irradiation at fairly high frequencies, either alone, or followed by root planing, did not provide achieve a clean and smooth root surface according to studies on extracted teeth by Morlock et al (25).…”
mentioning
confidence: 94%
“…28 Unlike high-level lasers, photodynamic therapy can selectively target the bacteria without potentially damaging the host tissues. 29 The photosensitizer is placed directly in the periodontal and peri-implant pocket and the liquid agent can easily access the whole root or implant surface before activation by the laser light through placement of the optical fiber directly in the pocket. As a result of the technical simplicity of the method and the high effectiveness of bacterial killing, the application of antimicrobial photodynamic therapy in the treatment of periodontal and peri-implant diseases has recently been studied extensively.…”
Section: Application Ofpdt In Periodontics and Implantsmentioning
confidence: 99%
“…However, melting of calculus and thermal damage was noted in localized areas of cementum and even dentin. Morlock et al ( 1992) showed that the Nd:YAG laser at 1.25-1.50 W, pulse 20 Hz, produced surface pitting and crater formation with charring, carbonization, melting, even when irradiation was performed parallel to root surface. Other authors demonstrated how the root surface was modified by Nd:YAG irradiation in a way that affected fibroblast recolonization and reattachment.…”
Section: Periodontal Applications Of Nd:yag Lasermentioning
confidence: 99%